2013
DOI: 10.1038/cdd.2013.50
|View full text |Cite
|
Sign up to set email alerts
|

Glycobiology of cell death: when glycans and lectins govern cell fate

Abstract: Although one typically thinks of carbohydrates as associated with cell growth and viability, glycosylation also has an integral role in many processes leading to cell death. Glycans, either alone or complexed with glycan-binding proteins, can deliver intracellular signals or control extracellular processes that promote initiation, execution and resolution of cell death programs. Herein, we review the role of glycans and glycan-binding proteins as essential components of the cell death machinery during physiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(59 citation statements)
references
References 120 publications
1
58
0
Order By: Relevance
“…This protein can be expressed and affect chemoresistance, resulting from induction by several signaling pathways required for CSC survival, such as IL-4 [46], Akt/PKB signaling [47], or Aurora-A [48]. Galectin-3 has been demonstrated to form heterodimers with Bcl-2, or may directly interact with the mitochondrial permeability transition pore complex and regulate its opening, preventing the release of cytochrome c [49, 50]. Moreover, galectin-3 can also inhibit cisplatin-induced poly(ADP-ribose) polymerase degradation and apoptosis, without alter Bcl-2, Bcl-XL, or Bax expressions [29].…”
Section: Discussionmentioning
confidence: 99%
“…This protein can be expressed and affect chemoresistance, resulting from induction by several signaling pathways required for CSC survival, such as IL-4 [46], Akt/PKB signaling [47], or Aurora-A [48]. Galectin-3 has been demonstrated to form heterodimers with Bcl-2, or may directly interact with the mitochondrial permeability transition pore complex and regulate its opening, preventing the release of cytochrome c [49, 50]. Moreover, galectin-3 can also inhibit cisplatin-induced poly(ADP-ribose) polymerase degradation and apoptosis, without alter Bcl-2, Bcl-XL, or Bax expressions [29].…”
Section: Discussionmentioning
confidence: 99%
“…Tumorigenic cells possess the change of glycosylation modification, which may lead to metastasis, uncontrolled proliferation, and the inhibition of apoptosis. [14][15][16] It has been reported that protein glycosylation was involved in potentially all aspects of human growth and development. Altered glycans on the tumor-and host-cell surface and in the tumor microenvironment have been identified to mediate critical events at the onset and/or during tumor progression.…”
Section: Introductionmentioning
confidence: 99%
“…42 We can also speculate that N-acetylglucosaminyltransferase GCNT3 contributes to the glycosylation of TRAIL receptors, which is critical for their function. 43,44 In addition, substance P stimulates p21-activated kinase, 45 which is a known regulator of the mitogen-activated protein kinases (MAPK) cascade. 46 In turn, MAPKs, at least in some cases, may sensitize cells to TRAIL-induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%